Building Students' Morality Through Tasawuf Akhlaki in Madrasah Ibtidaiyah - Dwi Safitri Wulandari, Siti; Aini Fahma, Mirda; Hidayati Lestari, Fitri; Romadhon Habibullah, Muhammad (Journal of Asian Primary Education (JoAPE), 2024)
Moral education has become a universal social phenomenon in the modern era. Nearly all modern societies tend to view moral education as an urgent and integral part of the education system. Moral awareness is a crucial aspect of education that influences the character development of students. The purpose of this study is to describe the process of building students' morality through Tasawuf Akhlaki. The method employed in this research is a literature review, which relies on sources such as books, journals, articles, official websites, and other internet-based references related to morality. This approach aims to provide readers with insights and a deeper understanding of the subject.